Direct Ink Writing of DNTF Based Composite with High Performance. Issue 8 (24th July 2018) - Xu, Chuanhao; An, Chongwei; He, Yining; Zhang, Yuruo; Li, Qianbing; Wang, Jingyu
Abstract: Direct ink writing (DIW) of energetic materials has been an area of interest for micro size charge. In this work, 3, 4‐dinitrofurazanofuroxan (DNTF) based composite was prepared with nitrocotton (NC) and Viton as binders by DIW. Scanning Electro Microscope (SEM) and X‐ray diffraction were employed to characterize the composite samples. The impact sensitivity and thermal decomposition of the composites were also tested and analyzed. In addition, the critical size of detonation and detonation velocity were measured. The results show that DNTF based composite has a high density with whose value is 1.785 g cm −3, reaching 93.16 % of theoretical maximum density (TMD). The particles in composites are spheroidal with size ranging from 1 to 2 μm. Compared with raw DNTF, the obtained composite has a lower impact sensitivity and higher thermal stability. Moreover, the composites exhibit excellent detonation properties, whose critical size of detonation is around 0.01 mm and the mean detonation velocity is 8580 m s −1 at the charging width of 1 mm. Furthermore, part performances of this composite are contrasted with previous reported CL‐20 based composite and show better characters. Abstract :